MATERNAL ADVERSE OUTCOMES OF TEENAGE PREGNANCY: A CROSS-SECTIONAL STUDY FROM PESHAWAR - Samreen Gul; Syed, Wajeeha; Saira Saira; Nazia Liaquat (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the adverse maternal outcome in teenage pregnancies reported to a tertiary care hospital in Peshawar. Methodology: A descriptive cross-sectional study was conducted among 177 females (15-19 years of age) and gestational age of more than 28 weeks was confirmed through ultrasonography. Adverse maternal outcomes such as anemia, eclampsia, pre-eclampsia, preterm deliveries, and lower segment cesarean section (LSCS) were measured as per defined in the operational definition. Maternal outcomes were stratified among residence and educational level to see effect modifiers. Results: In this study, anemia was detected in 45 (25.4%) patients while eclampsia and pre-eclampsia were noted in 44 (24.9%) and 45 (25.4%) patients respectively. Pre-term delivery and LSCS were observed in 79 (44.6%) and 53 (29.9%) patients respectively. Lower educational level was associated with eclampsia, preterm delivery, and lower segment cesarean section. Conclusion: Teenage pregnancy was reported to be related to a high rate of adverse maternal outcomes like anemia, eclampsia, pre-eclampsia, premature birth, and LSCS.